Analysis of some chemical methods for determination of penicillins - Cheng, Wing Hung E.
As pure crystalline penicillin is available, many chemical methods can be applied accurately. Since then, some titrimetric procedures have been proposed, and followed by those instrumental methods including spectrophotometry, fluorimetry, and colorimetry.